The Role of Law in the Digital Technology Era through Physical Education and Sports in Preventing Cybercrime in Adolescents in Schools - Harfiyana; Ismayani; Dewi Robianti (Journal Physical Health Recreation (JPHR), 2025)
This study aims to analyze the role of law in the digital technology era through physical education and sports (PJOK) towards preventing cybercrime among adolescents in schools using a qualitative case study. The research method involved participant observation in two public vocational high schools in Medan, in-depth interviews with 12 PJOK teachers and 3 IT legal experts, and focus group discussions with 25 students in grades X-XI (aged 15-17 years). Data were collected over a period of 4 months using semi-structured interview guidelines, PJOK digital literacy class observation sheets, and curriculum documents. The analysis was conducted using thematic analysis using NVivo 12 through open, axial, and selective coding processes. The results show four main themes: (1) integration of cyber law in PJOK subjects through virtual sports simulations (cyber football); (2) development of digital ethics through sports teamwork (responsibility awareness 82%); (3) prevention of cyberbullying through sports leadership training (incident reduction 67%); (4) school regulations based on UU ITE No. 11/2008 adapted in the school's digital sports code of ethics. The findings revealed that the Physical Education and Health Sciences (PJOK) approach effectively reduced cyber-risk behavior by 54% through a sports simulation that taught the consequences of digital law. The study concluded that the role of law through PJOK has the potential to be an innovative cybercrime prevention model, with a 91% student participation rate and a 73% increase in digital literacy.